ISOLATION OF LACCASE PRODUCING PHOMOPSIS SP.N7.2 - Phương Mai, Nguyễn Thị; Hoà, Lê Quang; Anh, Tô Kim (Vietnam Journal of Science and Technology, 2012)
SUMMARY Among 56 strains collected from degraded rice straw, paper and dye effluent samples, 38 strains were positively screened as potentially laccase producers on the solid medium added with enzyme indicators (tannic acid and RBBR) but only two were positive with Syringaldazine. The strains N 7.2 identified as Phomopsis sp. via analysis of its ITS sequence can achieve an laccase activity towards Syringaldazine up to 213,2 UI/ml after 6 days of cultivation. To date, this is the first report on the laccase from Phomopsis sp.